Analysis of the production of sweet orange "Pera Bianchi" as a function of the plant age and rainfalls - Tubelis, Antonio; Sobrinho, Joaquim Teófilo; Salibe, Ary Apparecido (Pesquisa Agropecuaria Brasileira, 1992)
This paper deals with the existence of empirical relationships between the production of "Pera Bianchi" sweet orange orchard, planted in Cordeirópolis, State of São Paulo, Brazil, with rainfalls that occurred before the picking season. The plants of sweet orange were budded on Rangpur lime rootstock, planted on Orto Dark-Red Latosol, at an altitude of 639 m above sea level. The climate of the experimental area is Cwa-warm climate with dry winter and hot summer. The orchard was conducted under conventional ways and no irrigation was applied. The behaviour of the production and its variations were analysed. It was noted that the production of the crop was correlated with the age of the orchard and with totals of rainfall that occurred in the nineteen months before the picking season. The production was correlated with the rainfall of two or more months of such period. There are twelve equations, presented that could be used to forecast the yield of the crop.